Development of Book Creator-Assisted E-Modules on Earth’s Shape and Surface to Enhance Learning Motivation among Elementary School Students - Rilla Hafni Wahdaniyah; Zulherman (Postgraduate, University of Mataram, 2025)
Technological innovations in education have become a global trend aimed at improving student learning outcomes. One such innovation is the development of e-modules, which provide students with effective tools to engage with subject content. Book Creator is an application that facilitates the creation of interactive and dynamic e-modules. This study employed a Research and Development (R&D) approach using the ADDIE model Analysis, Design, Development, Implementation, and Evaluation—to develop an e-module on the topic of Earth's shape and surface. The study was conducted in two elementary schools with a sample of 120 fifth-grade students, divided into control and experimental groups. The e-module development was validated by experts in material content, media, and language. Data collection methods included observation, expert appraisal, and pre- and post-test assessments. The validation results demonstrated the feasibility of the e-module for use in enhancing students’ learning motivation, with validation scores of 69% from media experts, 93% from material experts, and 100% from language experts. These findings indicate that the Book Creator-assisted e-module is an effective instructional tool for improving learning motivation, particularly in the context of IPAS (Integrated Science and Social Studies) in elementary education.